2009
DOI: 10.1111/j.1945-5100.2009.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Extent of thermal ablation suffered by model organic microparticles during aerogel capture at hypervelocities

Abstract: Abstract-New model organic microparticles are used to assess the thermal ablation that occurs during aerogel capture at speeds from 1 to 6 km s −1 . Commercial polystyrene particles (20 µm diameter) were coated with an ultrathin 20 nm overlayer of an organic conducting polymer, polypyrrole. This overlayer comprises only 0.8% by mass of the projectile but has a very strong Raman signature, hence its survival or destruction is a sensitive measure of the extent of chemical degradation suffered. After aerogel capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Since the size and composition of the captured particles have been found to directly influence the heating and ablation during the capture process, smaller single grained projectiles should also be tested. Burchell, et al, found that at an impact speed of 6.1 km s À1 in aerogel, 54% of 20 lm polypyrrole coated, polystyrene particles survived (Burchell et al, 2009a). This is taken to indicate that even when smaller particles are capture in aerogel, there would be sufficient captured material from each particle to then test for organics with DART-MS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Since the size and composition of the captured particles have been found to directly influence the heating and ablation during the capture process, smaller single grained projectiles should also be tested. Burchell, et al, found that at an impact speed of 6.1 km s À1 in aerogel, 54% of 20 lm polypyrrole coated, polystyrene particles survived (Burchell et al, 2009a). This is taken to indicate that even when smaller particles are capture in aerogel, there would be sufficient captured material from each particle to then test for organics with DART-MS.…”
Section: Discussionmentioning
confidence: 93%
“…Laboratory impact experiments firing glycine grains into aerogel (Nixon et al, 2012) showed that in impacts at 6 km s À1 the captured grains had lost the majority of their pre-impact mass in the capture process, but no tests were carried out on the aerogel to determine where the missing material had gone or how it may have been processed in the impact event. Similarly, impacts on aerogel by polystyrene microparticles show that 84% of the mass is lost during capture at speeds of 6 km s À1 (Burchell et al, 2009a).…”
Section: Introductionmentioning
confidence: 96%
“…(the Stardust speed) to 4.5 km s À1 (as here) would have increased the surviving mass fraction from 16% to 49% (Burchell et al, 2009b). This method of dust collection (Tsou et al, 2003) on Stardust returned to Earth a cargo of dust with a very high scientific yield Burchell et al, 2009a).…”
mentioning
confidence: 74%
“…There are issues with contamination during manufacture and handling (see Tsou et al, 2003). Thermal modification and ablation during capture can however also present issues, with thin surface coatings lost for example (see Burchell et al, 2009b). Stardust did successfully collect indigenous organic material from the comet for analysis on Earth (see Keller et al, 2006;Sandford et al, 2006).…”
mentioning
confidence: 99%
“…But to overcome these critical limitations, core@shell composite particles with conductive PPy shells coated on inorganic [10][11][12][13][14][15][16][17][18][19][20][21][22][23] or polymeric cores have been the subject of numerous research works from the late 1980s. These PPycoated particles allow the creation of new polymeric materials have enormous scientific and technological interests following the development of visual biomedical diagnostics [12,38], conductive composites [19,24], conductive paints [46], anticorrosion coatings [34], stationary phase in liquid chromatography [47], conductive pigments [20] and hypervelocity experiments with microprojectiles of PPy mimicking solar dusts [27][28][29][30][31]. Addtionally PPy can be prepared in the form of reactive and functional copolymers for the immobilization of metallic nanoparticles and other nano-objects [12,14,48].…”
Section: Introductionmentioning
confidence: 99%